Headache after dural puncture subarachnoid hemorrhage posing as meningitis - Sahay, Nishant; Bara, Mamta; Bhadani, Umesh K.; Singh, Pallavi (International Surgery Journal, 2017)
Headache after neuraxial blocks is a common complication. This case discussion highlights an important diagnostic dilemma when a sentinel subarachnoid hemorrhage mimics meningitis after spinal anesthesia. A patient presented with features of meningismus after spinal anesthesia. To confirm diagnosis, a second dural tap was done which resulted in a frank sub-arachnoid hemorrhage. This correspondence highlight importance of early vascular imaging when a patient presents with atypical headache after a dural puncture.